A Rare Tumor in the Common Bile Duct: A Case Report - Mustafa Suker (Journal of Pancreatic Cancer, 2017)
Background: Lymphoepithelial-like carcinoma (LEC) is rarely found in organs outside the nasopharyngeal area. This is the first case report of Epstein–Barr virus (EBV)-associated LEC of the extrahepatic tract. As it is very difficult to distinguish between LEC and adenocarcinoma in the clinical presentation, this article can give more insight into how the pathological analysis can help with the diagnosis. Case presentation: A 37-year-old Caucasian male with a history of Crohn's disease and primary sclerosing cholangitis presented with cholestasis. A computed tomography scan revealed a tumor in the pancreatic head without invasion into the surrounding organs. The patient underwent an uncomplicated pylorus-preserving pancreaticoduodenectomy, with pathology revealing an epithelial carcinoma of the common bile duct with metastases in 4 of the 18 resected lymph nodes. In situ hybridization demonstrated extensive EBV positivity in the tumor cells, and in serum, positive IgG anti-EBV was found. The diagnosis of EBV-associated LEC was hereby confirmed. The postoperative course was uneventful and 18 months after surgery there is no recurrence. Conclusion: In the case of an epithelial tumor in the periampullary region, one should consider EBV-associated LEC as this tumor may have a lot of similarity with the adenocarcinoma but has lower rates of recurrence after surgery and better overall survival.